Effects of vitamin D supplementation on metabolic parameters, serum irisin and obesity values in women with subclinical hypothyroidism: a double-blind randomized controlled trial - Safari, Sara; Rafraf, Maryam; Malekian, Mahsa; Molani-Gol, Roghayeh; Asghari-Jafarabadi, Mohammad; Mobasseri, Majid (Frontiers in Endocrinology, 2023)
Purpose Subclinical hypothyroidism is an early, mild form of hypothyroidism that may progress to overt hypothyroidism if untreated. The current study aimed to assess the effects of vitamin D supplementation on hormonal (thyroid stimulating hormone [TSH], triiodothyronine, thyroxine, and free thyroxine) parameters, lipid profiles, serum irisin, and obesity indices in women with subclinical hypothyroidism. Methods The present randomized, double-blind, placebo-controlled clinical trial was carried out on 44 women with subclinical hypothyroidism. The participants were allocated to two groups (22 patients in each group) that received vitamin D (50,000 IU/week) or placebo for 12 weeks. Fasting blood samples, anthropometric and body composition measurements, physical activity levels, and dietary intakes were collected at baseline and at the end of the study. Results Vitamin D supplementation significantly decreased TSH, total cholesterol, and fat mass percentage, and significantly increased serum vitamin D and irisin levels and fat-free mass percentage compared to the control group (all, p<0.05). Changes in thyroid hormones, other lipid profiles, and anthropometric indices were not significantly different between the groups. Conclusion Our study indicates that vitamin D administration improves serum TSH, total cholesterol, irisin, and body composition in women with subclinical hypothyroidism. More well-designed clinical trials are required to confirm these findings and clarify the effects of vitamin D supplementation on both genders of patients. Clinical trial registration https://www.irct.ir/trial/57482, Identifier IRCT20100408003664N25.